2021
DOI: 10.1002/nop2.982
|View full text |Cite
|
Sign up to set email alerts
|

Stress management strategies and quality of life in undergraduate nursing and midwifery students in Poland: A pilot study

Abstract: To achieve the competency levels required to practice as a registered nurse or midwife, student nurses and midwives require in-depth theoretical knowledge and practical skills. To fulfil the requirements, they need to undergo numerous hours of theoretical and practical training (McCarthy et al., 2018). In the European Union Member States, basic nursing education is regulated by Directive 2005/36/ EC of the European Parliament and of the Council of 7 September 2005 on the recognition of professional qualificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…The study’s results align with earlier research [21], [22], [23] which indicates that individuals who handle stress well, whether consciously or not, are more likely to thrive in everyday situations.…”
Section: Resultssupporting
confidence: 90%
“…The study’s results align with earlier research [21], [22], [23] which indicates that individuals who handle stress well, whether consciously or not, are more likely to thrive in everyday situations.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, comparing present results on coping behaviors to the current state of research illustrates that previous studies also identified active or problem-focused coping [ 13 , 30 ] and seeking emotional or social support [ 13 , 30 , 31 ] as most commonly used coping behaviors among nursing and midwifery students. In contrast to present descriptive findings, another study showed that risk behaviors such as alcohol consumption were prevalent in student midwives, among others [ 29 ].…”
Section: Discussionsupporting
confidence: 64%
“…Few studies indicated that student midwives, on the one hand, exhibit detrimental, maladaptive behaviors in response to high psychological stress in the workplace, such as physical inactivity, unhealthy diets, and alcohol, tobacco, and cannabis use [ 28 ], and decreased attention to recreation [ 18 ]. On the other hand, further studies with student midwives indicated that also adaptive coping behaviors are applied in the face of high psychological stress [ 9 ], such as active coping, the use of emotional support, and positive appraisal [ 30 , 31 ]. Thereby, the use of adaptive or maladaptive coping behaviors depends on student’s circumstances, needs, and interrelated coping opportunities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For future research, it may be relevant to examine the role of these personal demands in the health impairment processes of both master students and employees. Moreover, it would be interesting for future research to investigate whether students with varying levels of personal demands and personal resources use different active coping and passive strategies (e.g., Kowalska & Szwamel, 2022) to deal with stress, or whether different coping strategies are more or less effective for students scoring high on personal resources versus personal demands.…”
Section: Discussionmentioning
confidence: 99%